Beadle's Dime Book of Practical Etiquette for Ladies and Gentlemen : Being a Guide to True Gentility and Good-Breeding, and a Complete Directory to the Usages and Observances of Society - Anonymous (Salt Lake City, UT : Project Gutenberg, 2014)
"Beadle's Dime Book of Practical Etiquette for Ladies and Gentlemen" by Anonymous is a guide on social manners written in the mid-19th century. This manual addresses the intricacies of social interactions, including the etiquette of various occasions such as balls, dinner parties, and business interactions, aiming to cultivate good breeding and true gentility among its readers. With advice on dress, conversation, and proper introductions, it seeks to provide the knowledge required to navigate society with confidence and respect. The opening of the book introduces the fundamental theme of etiquette as essential to one's social success, emphasizing that true politeness is a reflection of character. It utilizes the anecdote of a character named Falconbridge, who experiences a series of embarrassing blunders during his initial foray into society due to his ignorance of social norms. This narrative sets the stage for an exploration of the skills necessary to engage gracefully in social environments, highlighting the importance of self-possession and confidence as one prepares to embrace societal expectations. (This is an automatically generated summary.)
Release date is 2014-05-05
E-text prepared by David Edwards, Emmy, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Etiquette